2021
DOI: 10.1080/03007995.2021.1976126
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous immunotherapy takes more than the time in the clinic

Abstract: Objective: The aim of this study was to investigate the time use and both direct and indirect costs associated with subcutaneous immunotherapy (SCIT) for adults with allergic rhinitis (AR) and caregivers of children with AR in the US. Methods: We conducted a survey to assess the retrospective time use and direct costs of SCIT. The populations surveyed included adults and caregivers of children (aged 5-17) with symptomatic AR of moderate or higher severity who are currently receiving or have previously started … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The time-use and direct cost of SCIT were investigated using an electronic survey prepared in Spanish. The survey has previous been used in the US [22]. Respondents were asked to recall their last SCIT visit; hence, all results are self-reported.…”
Section: Methodsmentioning
confidence: 99%
“…The time-use and direct cost of SCIT were investigated using an electronic survey prepared in Spanish. The survey has previous been used in the US [22]. Respondents were asked to recall their last SCIT visit; hence, all results are self-reported.…”
Section: Methodsmentioning
confidence: 99%
“…21 Previous research has shown diverse patients preferences and benefits of the different AIT treatments. 15,[22][23][24][25][26] Mode of administration, efficacy, risk of adverse events, and direct and indirect expenditures may determine which AIT patients prefer. 15 In this regard, SCIT treatment is burdensome due to time spent on each appointment and travel expenses, affecting patients' adherence.…”
Section: Introductionmentioning
confidence: 99%
“…15 In this regard, SCIT treatment is burdensome due to time spent on each appointment and travel expenses, affecting patients' adherence. 22 Despite the potential benefits of shared AIT decision-making, a physicians' guide on patient-related criteria and preferences is missing. Furthermore, AIT prescription patterns and patient preferences seem disconnected.…”
Section: Introductionmentioning
confidence: 99%